2016
DOI: 10.1158/0008-5472.can-15-3465
|View full text |Cite
|
Sign up to set email alerts
|

MYC Is a Crucial Mediator of TGFβ-Induced Invasion in Basal Breast Cancer

Abstract: Basal subtype breast cancers have a particularly poor prognosis, with high invasiveness and resistance to most targeted therapies. TGFβ and MYC drive central features of basal breast cancer: TGFβ is an autocrine and paracrine signaling factor that drives cell invasion and metastasis, and MYC is a central regulator of cellular proliferation that is upregulated in many cancer types. We show here that genetic or pharmacological inhibition of MYC in MCF10A basal breast cells results in increased sensitivity to TGF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…37 Furthermore, MDA-MB-231 cell line is a basal type while SK-BR-3 is a luminal-type breast cancer cell line, 38 and it has been shown that inhibition of MYC in basal-type BC cells by genetic or pharmacological methods leads to higher sensitivity to TGFβ-stimulated invasion and metastasis. 39 The same study also reported that the mentioned signaling loop only exists in basal BC cells, but not in luminal BC cells. Therefore, suppression of TGFβ members by miR-16 may counteract the TGFβ-MYC axis in MDA-MB-231 cells, which are basal-type BC cells, and this may be an important reason for inhibition of invasion as we detected by the invasion assay.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…37 Furthermore, MDA-MB-231 cell line is a basal type while SK-BR-3 is a luminal-type breast cancer cell line, 38 and it has been shown that inhibition of MYC in basal-type BC cells by genetic or pharmacological methods leads to higher sensitivity to TGFβ-stimulated invasion and metastasis. 39 The same study also reported that the mentioned signaling loop only exists in basal BC cells, but not in luminal BC cells. Therefore, suppression of TGFβ members by miR-16 may counteract the TGFβ-MYC axis in MDA-MB-231 cells, which are basal-type BC cells, and this may be an important reason for inhibition of invasion as we detected by the invasion assay.…”
Section: Discussionmentioning
confidence: 82%
“…MDA‐MB‐231 is a TGFβ1 responsive cell line while SK‐BR‐3 cells are TGFβ1 resistance . Furthermore, MDA‐MB‐231 cell line is a basal type while SK‐BR‐3 is a luminal‐type breast cancer cell line, and it has been shown that inhibition of MYC in basal‐type BC cells by genetic or pharmacological methods leads to higher sensitivity to TGFβ‐stimulated invasion and metastasis . The same study also reported that the mentioned signaling loop only exists in basal BC cells, but not in luminal BC cells.…”
Section: Discussionmentioning
confidence: 88%
“…Despite the importance of metastasis in the prognosis of cancer, a detailed molecular understanding of what fuels the ability of tumor cells to invade across basement membranes and disseminate to distant organs is still lacking (13). A role of Myc in this process has remained controversial in the literature (37), as oncogenic Myc has been linked to inhibition of tumor cell invasion via suppression of Jun N-terminal protein kinase (JNK) activity (38) or sensitization to transforming growth factor ␤ (TGF-␤) signaling (39). Conversely, the data presented here showing that Myc transcriptionally controls an integrated cellular machinery for mitochondrial movements, which in turn fuels cell motility and invasion (20), points to this pathway as a ubiquitous aspect of Myc-driven tumors, important for metastatic competence, in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing these three PI3K pathway activity groups to the pathway activity profiles found in other sets of breast cancer tumors [34], group 1 with low PI3K pathway activity seems to most closely resemble the luminal A breast cancer subtype with nearly half of the samples having high ER pathway activity, low PI3K and low TGFβ pathway activity. The third group (putative PI3K pathway activity with cellular oxidative stress), despite eight (32%) samples with a high ER pathway activity, shows distinct features that have been described in triple-negative tumors, i.e., TGFβ activity and oxidative stress [4,29,35]. TGFβ is thought to exert its tumor promoting effects through induction of EMT in cancer cells, a process which may be promoted by cellular oxidative stress, and associated with aggressive tumor pathology and bad prognosis [4,[29][30][31]33,36,37].…”
Section: Signal Transduction Pathway Combinationsmentioning
confidence: 94%